The complete chloroplast genome of Flemingia macrophylla (Willd.) Prain (Fabaceae) from Guangxi, China. Issue 12 (2nd December 2021) - Qin, Xin-mei; Li, Hong; Cui, Nan; Jiang, Shui-Yuan; Liang, Yan-Ni; Wang, Man-Lian; Huang, Xi-Yang
Abstract: Flemingia macrophylla (Willd.) Prain is an ethnomedicinal plant with high nutritional and medicinal values. In this study, we report the complete chloroplast genome of F. macrophylla . The chloroplast genome has a typical quadripartite structure with a genome size of 152, 988 bp, including a large single-copy (LSC) of 83, 634 bp, a small single-copy (SSC) of 17, 774 bp and two inverted repeats (IRs) of 25, 790 bp. The genome contains 129 genes, including 84 protein-coding, 37 tRNA and 8 rRNA genes. The overall GC content is 35.1%. Phylogenetic analysis showed that F. macrophylla grouped with a clade containing the genera of Fagelia, Dolichos, Eriosema, Dunbaria and Cajanus in Fabaceae. This study provides essential data and insight for understanding the phylogenetic placement of Flemingia .